Cover Image. (December 2016) - Temmerman, Andy; Vandessel, Jeroen; Castro, Ana; Jacobs, Reinhilde; Teughels, Wim; Pinto, Nelson; Quirynen, Marc
Abstract : The cover image, by Andy Temmerman et al., is based on the Randomized Clinical Trial The use of leucocyte and platelet‐rich fibrin in socket management and ridge preservation: a split‐mouth, randomized, controlled clinical trial, DOI:10.1111/jcpe.12612 .